Antitumor properties of griseofulvin and its toxicity - Yu, Nanqiong; Fu, Yixiao; Fan, Qingkui; Lin, Li; Ning, Zhifeng; Leng, Dongze; Hu, Meichun; She, Tonghui (Frontiers in Pharmacology, 2024)
Griseofulvin (GF), which mainly extracted from Penicillium griseofulvum, is a heat-resistant, chlorine-containing non-polyene antifungal antibiotic. Previous research shows GF has a variety of pharmacological effects, such as anti-inflammatory, antifungal, antiviral, anti-tumor and so on. In recent years, GF has received extensive attention on antitumor effects as a natural compound with low price, wide range of uses and other characteristics. However, there is no comprehensive review of GF pharmacological activity on anti-tumor has been published so far. In order to fully elucidate the antitumor activities of GF, this review focuses on the antitumor potential and toxicity of GF and its derivatives, based on a literature search was conducted using PubMed, Web of Science and other databases, to lay a good foundation for the further research of GF and the development of new drugs on antitumor.